THE DEVELOPMENT OF INTERACTIVE ELECTRONIC BOOK (BUDIN) USING FLIP PDF PROFESSIONAL TO TRAIN HIGHER ORDER THINKING SKILLS - ARINI, DIAH (Inovasi Pendidikan Fisika, 2017)
The main purpose of the research is to produce Interactive Electronic Book (BUDIN) using Flip PDF Professional which is valid, practically, and effectiveness. Validity is based on validity of learning, material, and media; practically is based on the implementation and constraints of learning; and effectiveness is based on higher order thinking skills and responses. Type of research is development using ADDIE model (Analysis, Design, Develop, Implement, Evaluate) and the subject of research is 19 student of Dharma Wanita Surabaya high school (XI grade of Science). The technique of data collection are questionare, observation, and test. Interactive Electronic Book (BUDIN) declared feasible if the percentage of validity (learning,material, media); practically (learnings implementation and constraints), and effectiveness (higher order thinking skills and students response) ≥61% with good and excellent category. The result of the research showed that the validity of interactive electronic book (BUDIN) are excellent (learning 97,92%;material 95,00%; media 93,75%); the practically is excellent (learnings implementation 94,07%) and effectiveness are good based on higher order thinking skills (analysis 78,94%, evaluate 73,68%, creation (structure 77,47%, fluency and flexibility 75,95%, link 75,21%, and novelty 73,68% )) and students responses is excellent with percentage between 84,21% to 94,74%. The conclusion of the research is that interactive electronic book (BUDIN) using Flip PDF Professional is feasible of being used to train higher order thinking skills. Keywords: Interactive Electronic Book (BUDIN), Higher order thinking skills, Flip PDF Professional